2014
DOI: 10.1371/journal.pone.0114772
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lifestyle Modification Programs on Cardiac Risk Factors

Abstract: Medicare conducted a payment demonstration to evaluate the effectiveness of two intensive lifestyle modification programs in patients with symptomatic coronary artery disease: the Dr. Dean Ornish Program for Reversing Heart Disease (Ornish) and Cardiac Wellness Program of the Benson-Henry Mind Body Institute. This report describes the changes in cardiac risk factors achieved by each program during the active intervention year and subsequent year of follow-up. The demonstration enrolled 580 participants who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…The results of the current study showed a significant difference in physical aspect, including physical functioning, role constraints due to physical problems, physical pain, life expectancy, vitality, and social performance, between the intervention and control groups following the lifestyle education to the intervention group based on ITM (Hefzalsehe), which was consistent with the findings of the study by Razavi et al, showing that lifestyle education was effective in reducing the risk factors of coronary artery diseases (12) and the results of the study by Loveman et al, on the clinical efficacy of type 2 diabetes education, which reported a significant improvement in metabolic control or quality of life as well as other mental parameters in the patients receiving such educations (13).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the current study showed a significant difference in physical aspect, including physical functioning, role constraints due to physical problems, physical pain, life expectancy, vitality, and social performance, between the intervention and control groups following the lifestyle education to the intervention group based on ITM (Hefzalsehe), which was consistent with the findings of the study by Razavi et al, showing that lifestyle education was effective in reducing the risk factors of coronary artery diseases (12) and the results of the study by Loveman et al, on the clinical efficacy of type 2 diabetes education, which reported a significant improvement in metabolic control or quality of life as well as other mental parameters in the patients receiving such educations (13).…”
Section: Discussionsupporting
confidence: 92%
“…LSM is especially important in patients with diagnosed CAD who have undergone surgery/intervention 9, 10. Many studies have revealed that sustained LSMs have a significant impact on reducing major adverse cardiac events (MACEs) after acute coronary syndrome (ACS) and coronary intervention 11, 12, 13. Also, after major events such as ACS and/or percutaneous transluminal coronary angioplasty (PTCA), developing a habit of regular blood pressure (BP) and blood glucose (BG) checkup is also an important modification which is necessary for patient's life 14, 15…”
Section: Introductionmentioning
confidence: 99%
“…[26] Also Ravazi et al (2014) on a three, twelve and twenty four-month follow up study with 580 participants, observed significant improvements in the decrease of BMI (p < .001 in all the evaluation moments), when evaluating the results of two lifestyle change programs (based on changes in eating habits, physical exercise and stress, amongst other things). [27] In the same way, the study previously referenced, conducted by Luisi et al (2015) demonstrated the important role of individualised educational intervention in the reduction of BMI. [19] Reveles (2015) also presented results showing a significant decrease of BMI (p < .012) and WC (p < .027), in the Portuguese study of 24 individuals with acute coronary syndrome who were followed-up on for six months in an educational nursing intervention program, when compared to the group not submitted to the program.…”
Section: Discussionmentioning
confidence: 68%